CYCLIC MONOTERPENOID PYRANOCARBAZOLE ALKALOIDS FROM THE BARK OF Murraya koenigii (L.) SPRENG (Jurnal Teknologi (Sciences & Engineering), 2015)
Murraya koenigii, locally known as "kari" tree, was selected for the phytochemical analysis. The extraction and isolation of the carbazole alkaloids from its n-hexane extract of the bark was carried out by using various chromatographic techniques. Three cyclic monoterpenoid pyranocarbazole alkaloids namely, murrayazolinol, murrayakoeninol and bicyclomahanimbine, were isolated. Their structures were determined on the basis of 1D-, 2D-NMR, IR, UV and mass spectrometry, and by comparison with the data from literature.
Keywords: Rutaceae; Murraya koenigii; pyranocarbazole alkaloids; phytochemicals